Comparison of staff and resident health status ratings in care homes. Issue 1 (17th March 2020) - Benson, Tim; Bowman, Clive
Abstract : Background: Many care home residents cannot self-report their own health status. Previous studies have shown differences between staff and resident ratings. In 2012, we collected 10 168 pairs of health status ratings using the howRu health status measure. This paper examines differences between staff and resident ratings. Method: HowRu is a short generic person-reported outcome measure with four items: pain or discomfort (discomfort), feeling low or worried (distress), limited in what you can do (disability) and require help from others (dependence). A summary score ( howRu score) is also calculated. Mean scores are shown on a 0–100 scale. High scores are better than low scores. Differences between resident and staff reports (bias) were analysed at the item and summary level by comparing distributions, analysing correlations and a modification of the Bland-Altman method. Results and conclusions: Distributions are similar superficially but differ statistically. Spearman correlations are between 0.55 and 0.67. For items, more than 92.9% of paired responses are within one class; for the howRu summary score, 66% are within one class. Mean differences (resident score minus staff score) on 0–100 scale are pain and discomfort (−1.11), distress (0.67), discomfort (1.56), dependence (3.92) and howRu summary score (1.26). The variation is not the same for different severities. At higher levels of pain and discomfort, staff rated their discomfort and distress as better than residents. On the other hand, staff rated disability and dependence as worse than did residents. This probably reflects differences in perspectives. Red amber green (RAG) thresholds of 10 and 5 points are suggested for monitoring changes in care home mean scores.